Influence of agglomeration and selection effects on the Chinese construction industry. Issue 1 (24th September 2020) - Zhang, Jingxiao; Zhang, Yuhuan; Philbin, Simon P; Ballesteros-Pérez, Pablo; Ouyang, You; Cheng, Jiawei
Abstract : The determination of whether market size can influence industrial agglomeration or selection is an important topic in economic development. To analyse the differential economic development of the construction industry under different market sizes, this research analyses the employment density of China's provinces and their total factor productivity (TFP). It also analyses whether the differences in the provinces' productivity are explained by their agglomeration and selection effects. First, a data envelopment analysis–Malmquist model is used to calculate the TFP of each construction industry sub-sector. Then, a nested model is used to measure the influence of the selection and the agglomeration effects on the TFP at different market sizes of the construction industry. Results evidence that there are significant differences in the construction productivity of different sub-sectors in different regions of China. These differences are mainly the consequence of the agglomeration effect, rather than the selection effect. Findings of this study suggest that the Chinese construction industry should optimise its structure in different provinces to achieve a balanced growth at different market sizes.